1986
DOI: 10.1159/000167108
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Plasma Arginine Vasopressin in Patients with Chronic Renal Failure Maintained on Hemodialysis

Abstract: Plasma arginine vasopressin (PAVP) was studied in patients before and after hemodialysis. The levels of PAVP were higher before and reverted to normal range after dialysis (5.7 vs. 2.7 pg/ml). Sequential chemical dialysis showed that vasopressin was removed during the chemical dialysis phase. Data obtained during a simulation experiment were also consistent with the view that vasopressin was removed during the chemical dialysis phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Other stimuli for the release of AVP during HD include nausea and pain related to puncture of the fistula. The effect of conventional HD on plasma osmolality is not well delineated, with some studies reporting no change [29,34] and others reporting a decrease in plasma osmolality [15,35,36,37,38,39,40,41,42,43,44]. Table 1 summarizes the theoretical effects of HD on AVP release.…”
Section: Stimuli For Avp Release During Hdmentioning
confidence: 99%
See 3 more Smart Citations
“…Other stimuli for the release of AVP during HD include nausea and pain related to puncture of the fistula. The effect of conventional HD on plasma osmolality is not well delineated, with some studies reporting no change [29,34] and others reporting a decrease in plasma osmolality [15,35,36,37,38,39,40,41,42,43,44]. Table 1 summarizes the theoretical effects of HD on AVP release.…”
Section: Stimuli For Avp Release During Hdmentioning
confidence: 99%
“…Plasma AVP levels in patients varied widely, with some studies reporting pre-HD plasma AVP levels above the concentration regarded as the upper level of normal of 4 pg/ml [2,16,24,25,35,37,38,39,40,41,45,46,47,48,49,50,51,52,53,54], while others found pretreatment plasma AVP levels around or below 4 pg/ml [32,33,34,43,44,55,56,57] (fig. 3a).The variation in pretreatment plasma AVP levels might be due to analytical variation resulting from the use of different assays.…”
Section: Plasma Vasopressin Levels In Dialysis Patients and Healthy Imentioning
confidence: 99%
See 2 more Smart Citations
“…The 1. Abbreviations used in this paper: AC, adenylyl cyclase; AVP, arginine vasopressin; CCT, cortical medullary collecting tubule; CRF, chronic renal failure; CT, cholera toxin; IMCD, inner medullary collecting duct; IMCT, inner medullary collecting tubule; PKC, protein kinase C; PM, plasma membrane; PT, pertussis toxin; RT, reverse transcription; V2R, V2 receptor. urinary concentrating defect in uremia is not due to deficient arginine vasopressin (AVP) secretion from the pituitary gland as both the neurophysin for AVP (3) and AVP itself (4) are found in increased quantity in the sera of patients with CRF. Furthermore, Tannen et al have demonstrated persistent excretion of hypotonic urine by patients with CRF despite the administration of exogenous AVP (5) suggesting that the concentrating defect is at least in part due to impaired AVP responsiveness of the collecting duct.…”
Section: Introductionmentioning
confidence: 99%